Phase control of the transient resonance of the automatic ball balancer. (May 2016) - Michalczyk, Jerzy; Pakuła, Sebastian
Abstract: Hazards related to undesired increases of vibration amplitudes in transient resonance of vibroinsulated rotor systems with automatic ball balancer (ABB) are discussed in the paper. The application of the phase control method with taking into account the limited drive power is proposed for these amplitudes reduction. The high efficiency of this approach is indicated. Highlights: We modelled mechanical system of rotor machine with synchronous eliminator. Simulation results of starting unbalanced rotor machine using phase control method. Phase control of the transient resonance is a effective method to reduction maximal amplitude. Switching times are significant in performance of phase control method.